2013
DOI: 10.1002/wene.71
|View full text |Cite
|
Sign up to set email alerts
|

Urban transport and CO2 emissions: some evidence from Chinese cities

Abstract: The work presented below was conducted as part of the World Bank's economic and sector work titled 'Urban Transport and Climate Change'. It is first a compendium of data-most of it collected as part of the 'China-GEF-World Bank Urban Transport Partnership Program'-and also provides a preliminary analysis of urban transport characteristics, energy use, and greenhouse gas (GHG) emissions for a diverse set of cities in China. This working paper is not in itself intended to be a strategy for urban transport and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…6 Over the last decade, significant carbon emission growth was registered for emerging economy megacities. A World Bank study showed that urban transport energy use and carbon emissions were growing by between 4 and 6 percent a year in the 2000s in Beijing, Guangzhou, Shanghai and Xian (Darido, Torres-Montoya et al 2009). Between 2005 and 2010, carbon emissions from transport in Shanghai even grew by 15 per cent annually, the highest growth rate of any sector (Li and Cao 2012).…”
Section: Carbon Emissions From the Provision Of Access In Citiesmentioning
confidence: 99%
“…6 Over the last decade, significant carbon emission growth was registered for emerging economy megacities. A World Bank study showed that urban transport energy use and carbon emissions were growing by between 4 and 6 percent a year in the 2000s in Beijing, Guangzhou, Shanghai and Xian (Darido, Torres-Montoya et al 2009). Between 2005 and 2010, carbon emissions from transport in Shanghai even grew by 15 per cent annually, the highest growth rate of any sector (Li and Cao 2012).…”
Section: Carbon Emissions From the Provision Of Access In Citiesmentioning
confidence: 99%
“…In the China context, although transit infrastructure development has boomed in recent years and transit tends to have a significant mode share in most cities (Darido, et al, 2010), walk access distances to transit -especially to the relatively new BRT systems -have rarely been explored. Cervero& Day (2008)and Pan, et al (2009) each use a 1-km threshold in models to estimate (rail) transit proximity effects on travel behavior and accessibility of residents in specific neighborhoods, yet neither study offers evidence to support the selection of this threshold.…”
Section: Backdrop: the Transit Station Catchment Area And The Role Ofmentioning
confidence: 99%
“…The mode of trip generation is changed in Beijing from cycling and walking to car and less part towards Public transportation (Darido et al, 2009). Environmental Protection Bureau of Beijing stated that "Beijing transportation emits one third locally caused PM 2.5 pollution (Eichhorst and Bongardt, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%